2010
DOI: 10.1002/ejoc.200901323
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Amino Nitriles from Carbonyl Compounds, Amines, and Trimethylsilyl Cyanide: Comparison between Catalyst‐Free Conditions and the Presence of Tin Ion‐Exchanged Montmorillonite

Abstract: In the absence of catalysts, the three-component, one-pot synthesis of α-amino nitriles proceeded using various aldehydes and ketones together with amines and trimethylsilyl cyanide (TMSCN) in high yields under neat conditions at room temperature. The addition order of the reagents had a significant influence on the yields of the desired α-amino nitriles. In contrast, when tin ion-exchanged montmorillonite (Sn-Mont), prepared by the ion-exchange of sodium montmorillonite (Na-Mont) with a tin tetrachloride solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 60 publications
1
30
1
Order By: Relevance
“…MMT is able to intercalate various ions into the interlayer spaces, which would influence the interlayer distance [20]. The 001 reflection of the XRD patterns showed the basal spacing of MMT ( Figure 1).…”
Section: Characterization Of Catalystmentioning
confidence: 99%
“…MMT is able to intercalate various ions into the interlayer spaces, which would influence the interlayer distance [20]. The 001 reflection of the XRD patterns showed the basal spacing of MMT ( Figure 1).…”
Section: Characterization Of Catalystmentioning
confidence: 99%
“…[25] They later found that its high specific surface area was formed by the intercalation of SnO 2 nanoparticles between clay layers, resulting in strong Brønsted and Lewis acidity. [26][27][28] Sn-MMT was also found to display a disorganized "house-of-cards" structure. [23] The coexistence of acid sites was leveraged for various hemicellulose upgrading reactions: conversion of carbohydrates to 5-(hydroxymethyl) furfural (HMF), [29] HMF self-etherification, [24] synthesis of alkyl lactates from triose [30] and the production of furfural from xylose.…”
Section: Introductionmentioning
confidence: 98%
“…reported that Sn‐MMT displayed a highly superior activity than Sn‐grafted MCM‐41 for the cyanosilylation of ketones . They later found that its high specific surface area was formed by the intercalation of SnO 2 nanoparticles between clay layers, resulting in strong Brønsted and Lewis acidity . Sn‐MMT was also found to display a disorganized “house‐of‐cards” structure .…”
Section: Introductionmentioning
confidence: 99%
“…25,28 Thus, the reaction pathway in the nucleophilic substitution of al- 20 followed by the direct attack with 1,3-dicarbonyl compounds to form the alkylated 1,3-dicarbonyl derivatives.…”
mentioning
confidence: 99%